Body Size and Risk of Spontaneous Abortion among Danish Pregnancy Planners. Issue 5 (September 2014) - Hahn, Kristen A.; Hatch, Elizabeth E.; Rothman, Kenneth J.; Mikkelsen, Ellen M.; Brogly, Susan B.; Sørensen, Henrik T.; Riis, Anders H.; Wise, Lauren A.
Abstract Background Several studies indicate that female obesity increases the risk of spontaneous abortion (SAB). Central adiposity, height, and location of typical weight gain have not been examined as risk factors for SAB. Methods We examined the associations between selected anthropometric factors and risk of SAB among 5132 women enrolled in a Danish Internet‐based prospective cohort study of pregnancy planners. We used Cox proportional hazards regression models, with gestational weeks as the time scale, to compute hazard ratios (HRs) of SAB and 95% confidence intervals (CIs). Results After adjustment for potential confounders, the HRs for SAB among underweight (body mass index (BMI, kg/m2) <20), overweight (BMI: 25–29) and obese (BMI ≥30) women were 1.00 [95% CI: 0.81, 1.24], 0.90 [95% CI: 0.73, 1.09] and 1.23 [95% CI: 0.98, 1.54], respectively, compared with normal weight women (BMI 20–24). The association between obesity and SAB was stronger for early SAB (<8 weeks gestation); HR: 1.34 95% CI: 1.01, 1.77. The HR for height ≥174 cm vs. <166 cm was 0.81 [95% CI: 0.66, 1.00]. Increased waist‐to‐hip ratio (WHR) was inversely associated with risk of SAB (HR: 0.81; 95% CI: 0.63, 1.05). Waist circumference and location of typical weight gain were not appreciably associated with SAB risk. Conclusions This study confirms previous studies that have shown a small positive association between obesity and SAB risk. Our results suggest that obesity is a stronger risk factor for early pregnancy losses, and that small stature and low WHR are associated with an increased risk of SAB.